User Acceptance Of MyKad As An E-Commerce Tool In Malaysia - Fadil, Farrah (2009)
This study attempts to answer two research questions; namely (1) What are the determinants that influence user\' acceptance of using MyKad as an e-commerce tool? and (2) How do the determinants that influence the users\' acceptance of MyKad as an e-commerce tool fits into the modified Technology Acceptance Model (ATM)?